IMPACT OF INSULIN RESISTANCE ASSESSED BY THE HOMA2-IR MODEL ON THE SEVERITY OF CORONARY ARTERY DISEASE IN NON-DIABETIC PATIENTS WITH ACUTE CORONARY SYNDROME (Vietnam Journal of Community Medicine, 2026)
Objective: This study aims to determine the prevalence of insulin resistance (HOMA2-IR) in non-diabetic patients with acute coronary syndrome and to evaluate its association with clinical characteristics, cardiac injury markers, the severity of coronary artery disease, and risk stratification parameters (GRACE and Gensini scores) during the acute phase.Methods: A cross-sectional analytical study was conducted on 116 non-diabetic patients with acute myocardial infarction. Insulin resistance was defined as HOMA2-IR ≥ 1,35. Clinical characteristics, biochemical parameters, Gensini score, and GRACE score were collected and compared between the groups with and without insulin resistance.Results: Among 116 non-diabetic patients with acute coronary syndrome, the prevalence of insulin resistance was 58.6%. Compared with the non-insulin-resistant group, patients with insulin resistance were younger (65.34 years vs. 70.75 years; p = 0.027), had a higher BMI (23.68 kg/m² vs. 21.75 kg/m²; p < 0.001), and exhibited significantly elevated fasting glucose and fasting insulin levels (p < 0.001). The insulin-resistant group also had higher systolic blood pressure, heart rate, and a greater proportion of patients with intermediate or high GRACE risk scores (p < 0.05). In addition, they had higher Gensini scores and longer lesion length (p < 0.05), increased hs-TroponinT and CK-MB levels (p = 0.03 and p = 0.04, respectively), and lower left ventricular ejection fraction (p = 0.02). Conversely, NT-proBNP levels did not differ significantly between the two groups.Conclusion: In this study, insulin resistance assessed by HOMA2-IR was highly prevalent among non-diabetic patients with acute coronary syndrome and was associated with higher GRACE risk scores, more severe coronary atherosclerotic burden, and reduced left ventricular ejection fraction. These findings suggest that insulin resistance may serve as an accompanying marker of a higher cardiovascular risk profile in this patient population. However, given the cross-sectional study design, these associations are observational only and should be confirmed in large, multicenter cohort studies.
Keywords: Insulin resistance, acute coronary syndrome, HOMA2-IR.